Napoleon and British Song, 1797-1822 - Cox Jensen, Oskar. author. aut Link
VIII, 261 p.
Keywords: This study offers a radical reassessment of a crucial period of political and cultural history. By looking at some 400 songs, many of which are made available to hear, and at their writers, singers, and audiences, it questions both our relationship with song, and ordinary Britons' relationship with Napoleon, the war, and the idea of Britain itself.